Job flows, returns to skill, and rent-sharing at the dawn of the new millennium: A firm-level inquiry from the BRICS - PANOS, GEORGIOS A.; YANG, YONG (International Journal of Language, Translation and Intercultural Communication, 2018)
We present a firm-level inquiry on labour-demand characteristics in the BRICS economies, using standardized data from the World Bank Enterprise Surveys for the pre-crisis period of 2002-2003. The BRICS countries are the growth champions of that period, with numerous discussions on the effect of growth on inequality and the role of skills on labour-market performance. We examine employment, employment growth and its constituents, as well the returns to skill and the incidence of rent-sharing. We find that SMEs in the BRICS exhibit lower gross employment growth, compared to large firms. Large firms in Brazil, Russia and South Africa are responsible for most of the net job creation. In contrast, small and medium firms in China and India exhibit higher net job creation rates compared to large firms. Younger firms in Brazil, Russia and India generate higher net job creation figures, in contrast to China and South Africa, in which it is the large firms that generate more net new jobs. Foreign firms in China exhibit the highest net job creation, while in Brazil and India domestic firms create most of the new net employment. Private firms are responsible for most of the net job creation and job reallocation in all BRICS counties. The returns to skill are lower in SMEs and young firms, and we find evidence in favour of rent sharing, particularly in Brazil and India, by foreign and exporting firms, and by SMEs in China.